Voegelin's Israel and Revelation: an interdisciplinary debate and anthology - Thompson, William M.; Morse, David Lee; Voegelin, Eric (Marquette studies in theology, 2000)
An Interdisciplinary Debate and Anthology -- Contents -- Preface -- Contributors -- Theme and Variations in VoegelinÌs -- Politics and the Transcendent: -- Revisiting VoegelinÌs -- VoegelinÌs Philosophy of History and Human Affairs: -- The Voegelinian Impulse -- Voegelin's Israel And Revelation after Forty Years: -- The Movement toward Personalism -- The Problem of Metastasis: Eric VoegelinÌs Reading of Isaiah -- Taming Israel: -- Christ and Christianity in -- Exodus and Statecraft: A Postlude -- Selections from -- References -- Index.